Things I wish I told my mother [large type] - Patterson, Sue; DiLallo, Susan, 1947-; Patterson, James, 1947- (Little, Brown and Company, 2023)
Laurie surprises her mother, "Dr. Liz", with a mother-daughter vacation in Paris, France--one that brings to light a lifetime of secrets.